A Study on Livelihood Vulnerability of Farmers: A Case Study of Aspirational Districts of Karnataka, India - Tarun Baparao Gorijavolu; Sidram BY; Devendra Beeraladinni; S.B. Goudappa; Ravi. M. Sambrani (Archives of Current Research International, 2024)
The study was conducted to access the livelihood vulnerability of the farmers in aspirational districts in Karnataka. Livelihood vulnerability refers to the susceptibility of individuals or communities to adverse impacts on their means of sustenance and economic well-being, often stemming from external shocks or stressors. An ex-post facto research design was used. A sample size of 120 respondents were selected from Raichur and Yadgir districts using a simple random sampling technique. A well-structured interview schedule and Livelihood Vulnerability Index (LVI) which includes eight components viz., Socio-demographic profile, livelihood strategies, social networks, food, water, health, climate variability and extremes, were use for data collection. Mean, cumulative frequency distribution and LVI were used for data analysis. The results revealed that the livelihood vulnerability index for Raichur was 0.484 and for Yadgir was 0.478. This indicates that the people in both districts are equally vulnerable to livelihood shocks and stresses. The medium level of LVI might be due to their dependency on more than one livelihood activities.